Accurate Ultrasound Indoor Localization Using Spring-Relaxation Technique - Chew MT; Alam F; Legg M; Sen Gupta G (MDPI (Basel, Switzerland), 2021)
This paper reports on the development of an ultrasonic sensing-based active localization system. The system employs an ultrasonic array to transmit chirp signals and time-of-flight measurement for ranging. The position of the receiver is estimated iteratively using the spring-relaxation technique. A median and 90-percentile error of 12.4 and 21.7 mm, respectively, were obtained for measurements at 625 positions within a 1.2 × 1.2 m area testbed. The spring-relaxation technique outperforms the widely adopted linear least square-based lateration technique while using the same ranging data. The performance of the system is benchmarked against that of visible light positioning using the same platform setup. The reported results show the ultrasonic system to be more accurate when compared with the visible light positioning system, which achieved median and 90-percentile errors of 33.7 and 58.6 mm, respectively.
Keywords: ultrasound indoor localization; spring-relaxation; linear least square lateration; visible light positioning; multipath; 0906 Electrical and Electronic Engineering